Hybrid Systems of Distributed Generation with Renewable Sources: Modeling and Analysis of Their Operational Modes in Electric Power System - A. M. Gashimov; N. R. Rakhmanov; S. T. Akhmedova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper considers problems pertaining to modeling and simulation of operational hybrid system modes of the distributed generation comprising conventional sources – modular diesel generators, gas-turbine power units; and renewable sources – wind and solar power plants. Operational modes of the hybrid system have been investigated under conditions of electrical connection with electric power system and in case of its isolated operation. As a consequence